Plasmodium falciparum translational machinery condones polyadenosine repeats - Slavica Pavlovic Djuranovic; Jessey Erath; Ryan J Andrews; Peter O Bayguinov; Joyce J Chung; Douglas L Chalker; James AJ Fitzpatrick; Walter N Moss; Pawel Szczesny; Sergej Djuranovic (eLife, 2020)
Plasmodium falciparum is a causative agent of human malaria. Sixty percent of mRNAs from its extremely AT-rich (81%) genome harbor long polyadenosine (polyA) runs within their ORFs, distinguishing the parasite from its hosts and other sequenced organisms. Recent studies indicate polyA runs cause ribosome stalling and frameshifting, triggering mRNA surveillance pathways and attenuating protein synthesis. Here, we show that P. falciparum is an exception to this rule. We demonstrate that both endogenous genes and reporter sequences containing long polyA runs are efficiently and accurately translated in P. falciparum cells. We show that polyA runs do not elicit any response from No Go Decay (NGD) or result in the production of frameshifted proteins. This is in stark contrast to what we observe in human cells or T. thermophila, an organism with similar AT-content. Finally, using stalling reporters we show that Plasmodium cells evolved not to have a fully functional NGD pathway.